Biological Consequences of Thrombin Receptor Deficiency in Mice - Darrow, Andrew L; Fung-Leung, Wai-Ping; Ye, Richard D; Santulli, Rosemary J; Cheung, Wai-Man; Derian, Claudia K; Burns, Carol L; Damiano, Bruce P; Zhou, Lubing; Keenan, Charlotte M; Peterson, Per A; Andrade-Gordon, Patricia (Thrombosis and Haemostasis, 1996)
The thrombin receptor (ThrR) is a membrane-bound, G-protein-coupled receptor for the serine protease thrombin. This receptor is expressed in a wide variety of cells and tissues, and elicits a range of physiological responses associated with tissue injury, inflammation, and wound repair. To achieve a better understanding of the physiological role of the ThrR, we have employed homologous recombination to create mice with a disrupted ThrR gene. Following heterozygous (+/-) intercrosses, a total of 351 surviving offspring were genotyped. Only 7% of these offspring were identified as homozygous (-/-) for the disrupted allele, indicating a profound effect on embryonic development. Paradoxically, adult ThrR-/- mice appeared to be normal by anatomical and histological analysis, including their platelet number and function. Similarly, ThrR deficiency had no detectable effect in adult ThrR-/- mice on basal heart rate, arterial blood pressure, vasomotor responses to angiotensin II and acetylcholine, and coagulation parameters, even though the ThrR is expressed in many cardiovascular tissue types. In addition, the loss of ThrR function in the peripheral vasculature of adult ThrR-/- mice was confirmed by the absence of various standard hemodynamic effects of the ThrR-activating peptides SFLLRN-NH2 and TFLLRNPNDK-NH2 Our results indicate that ThrR deficiency has a strong impact on fetal development; however, ThrR-/- mice that proceed to full development display surprisingly little change in phenotype compared to the wild-type